Health-saving technologies in educational process organization at medical university - Куцак, Алла Валеріївна; Kutsak, A. V.; Куцак, А. В. (Минск : БГУ, 2020)
The article reveals the management peculiarities of the educational process at university on the health-saving technologies principles, which contribute to maintaining health, increasing the students activity, ensuring the conditions for self-preparation. It was concluded that the role of educational programs aimed at preserving and strengthening future specialists health should become a priority in healthy lifestyle formation. The role of health-saving technologies in the future professional activity of medical students has been grounded. В статье раскрыты особенности управления учебно-воспитательным процессом в университете на принципах здоровьесохранных технологий, что способствует сохранению здоровья, увеличению активности студентов, обеспечению условий для самостоятельной подготовки к занятиям. Сделан вывод о том, что в формировании здорового образа жизни приоритетной должна стать роль образовательных программ, направленных на сохранение и укрепление здоровья будущих специалистов. Обоснованна роль здоровьесохранных технологий.
Здоровьесохранные технологии в организации учебно-воспитательного процесса в медицинском университете
Keywords: health-saving technologies; health-saving learning; motivation of healthy way of life; здоровьесохранные технологии; здоровьесохранное обучение; мотивация здорового образа жизни